La valutazione vista da lontano: lo sguardo della pedagogia generale (I) - Elsa Maria Bruni (LED Edizioni Universitarie, 2018)
This paper investigates the question of evaluation in relation to the individual's formation process and, as an inherent necessity in the educational process, the examination revolves round the problem of building knowledge and competences in all human beings. Commencing with the historical context, the aim of the investigation is to evidence the problematical issues that the practice of evaluating involves and eventually to outline an interpretative paradigm respectful of the learning processes of individuals who, during their lives, are involved in a continual reshaping of their cognitive potential both on a horizontal plane (in relation to contexts and formal, non formal and informal formative agencies) and on a vertical plane (as a permanent process linked to the different «ages» of their development and maturity). Hence, the reflection presents the main tendencies of evaluating interpretation in school contexts: in doing so, it makes the difficulties encountered by the traditional evaluating practice come to light, whilst outlining those possible paths of re-reading that aim to restore balance in the issue of the complex formation process and making evaluation a strategic moment that activates formation dynamics from the point of view of both cognitive process and personal development.